ENKAPSULASI EKSTRAK BUMBU GENEP MENGGUNAKAN TWEEN 80 SEBAGAI PENGEMULSI - Ni Luh Putu Ravi Cakswindryandani; Ryan Pieter Imanuel Nalle; Agustina Etin Nahas; Siska Elvani (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
Genep is a Balinese spice that is usually served for all Balinese dishes and is usually served in a wet form. Genep seasoning must be used until finished because it has a short shelf life. Genep seasoning is composed of turmeric, ginger, kencur, galangal, onion, garlic, pepper, coriander, candlenut, nutmeg, chili, shrimp paste, and salt. The content of bioactive compounds derived from the ingredients used makes genep seasonings susceptible to oxidation processes that result in decreased quality and shelf life of genep seasonings. This must be prevented by applying technologies such as encapsulation to increase the weakness of seasonings in the wet form. Genep seasoning is extracted to look for useful bioactive compounds and then encapsulated to maintain product quality. This study used concentration of Tween 80 as an emulsifier including 0%, 0.5%, 1%, 1.5%, and 2%. The best genep seasoning extract obtained from the best treatment was encapsulated using maltodextrin and the addition of tween 80 as a treatment that significantly affected yield, water content, solubility, color, and encapsulation efficiency. Encapsulation produces a brownish-yellow and bright product with a yield of 87,36%, a moisture content of 5.92% w / w, solubility of 94.23% w / k, brightness value (L *) 39.39, and an encapsulation efficiency of 83,83%. Tween 80 concentration is very influential on the characteristics of the even seasoning extract encapsulate where the higher Tween 80 concentration is able to increase yield, solubility, color brightness, encapsulation efficiency, and reduce water content.